Assessing the Extent of NCE Mathematics Education New Minimum Standard Implementation in Colleges of Education in Niger State, Nigeria - USMAN, Hassan (Ilorin Journal of Education, 2024)
The study seeks to assess the extent to which NCE Mathematics new minimum standard is been implemented in colleges of education in Niger state, Nigeria. Two objectives with corresponding research questions guided the study. The study adopts mixed-methods research design. The population of study encompasses 126 lecturers in Colleges of Education in Niger State. Using a purposive sampling technique, a total of 17 lecturers were selected from the mathematics departments of the two colleges: 9 from the College of Education, Minna, and 8 from the Federal College of Education, Kontagora. To gather data, two instruments were utilized: the NCE Mathematics Programme Implementation Questionnaire (NCEMPIQ) and an interview protocol to capture the perspectives of lecturers regarding the extent of Minimum Standard implementation. Experts validated the questionnaire, and to establish reliability with Cronbach's alpha, data was organized for analysis using SPSS statistical software its internal consistency was evaluated yielding a reliability coefficient of 0.79. Mean and standard deviation were employed for data analysis, with a criterion mean of 2.5 serving as the basis for assessment. The findings revealed that the new minimum standards for NCE mathematics education in Colleges of Education in Niger State is found to be successfully implemented. Hence, it was recommended among others that National commission for Colleges of Education should establish a monitoring and evaluation framework to track the progress of curriculum implementation and address challenges promptly.